"Seremos nosso porta-retrato e já estamos portando essa tela": miradas em nudes autopublicados no Tumblr Bucepowergang - Thereza Nardelli e Silva (2018)
If inequalities are present in the access and use of digital communication technologies, they also seem to resonate in the context of digital visual representations, in which bodies of women appear in online texts that circulate daily. In this place, photography, and especially the practice of shared self-portraits, plays an important role in the management of contemporary self-visualities. Popularly known as selfies, the digital self-portraits that circulate on digital social platforms have also gained importance in the creation of political texts. Bucepowergang, a blog hosted on Tumblr, offers a collection of nude selfies (or just nudes, known as selfies that present recognizable visual elements associated with a shared concept of nudity) are sent by women, housed in a textual network associated with body positivity and self-love themes. Such photographs, while exhibiting nude bodies, slide between aspects of pornographic language and its localized textual appropriation, in the emergence of self-visions that bestow upon themselves an engaged use. Faced with such complexity, we ask: How does the public self-inscription of body nudity, represented in nude photography, emerge in the processes of signification observable, through the composition of miradas present in the texts of the blog Bucepowergang? For this discussion, we start from conceptions about selfies and nudes as vernacular self-portrait forms of today, and locate their importance and use in the dissemination of feminine visuals in online environments. We also develop another core subjects for our research object. One of them is about perspectives on the representation of women in visual images, as well as, more specifically, on pornographic language, associated with different theoretical conceptions. Another, elaborates on digital technologies in the daily manufacture of images, and the specifics provided in the association between portability, screen, frontal camera and the quick access to the sharing in digital social platforms currently available in smartphone devices. For the analysis, we developed a methodology based mainly on the concepts of textuality and mirada, as developed by Abril. We conclude, after the qualitative analysis of five selected nudes, that the characteristic aspects of selfie as a contemporary photographic and media genre, facilitate the presentation of the self, and articulares a central role for the enunciation of marginal visualities in this blog.